Systemic inflammation among adults with diagnosed and undiagnosed cardiometabolic conditions: a potential missed opportunity for cardiovascular disease prevention - Mainous, Arch G.; Sharma, Pooja; Jo, Ara (Frontiers in Medicine, 2024)
Context: Systemic inflammation is associated with cardiovascular morbidity and mortality.Since inflammation isn't screened in the population, the prevalence, particularly among individuals with undiagnosed cardiometabolic disease, is unclear.Objective: To assess the prevalence of elevated inflammation using high sensitivity Creactive protein (hs-CRP) (>0.30 mg/dL) in adults with no cardiometabolic disease, undiagnosed disease and diagnosed disease. Methods: We conducted a cross-sectional analysis of the 2015-2020 National Health and Nutrition Examination Survey which allows for population estimates of the US population. Adults >= 20 years old were included. HsCRP levels >0.30 mg/dL represented inflammation. Individuals were classified into disease defined as having one or more of the following: diagnosed disease--diabetes, hypertension, hyperlipidemia, or obesity by diagnosis; undiagnosed disease (self-report of no doctor diagnosis but positive biomarker); no disease. Results: 12946 unweighted individuals representing 315,354,183 adults in the US population were assessed. The proportion of adults with systemic inflammation is 34.63%. The proportion of individuals aged 20 years and older with no disease, undiagnosed disease and diagnosed disease and inflammation was 15.1%, 29.1% and 41.8% respectively. When stratifying by race/ethnicity among individuals with elevated inflammation Non-Hispanic Black people have the highest prevalence (50.35%) in individuals with diagnosed disease followed by Hispanics (46.13%) and Non-Hispanic White people (40.15%) (p<0.01). In logistic regressions adjusted for sociodemographic variables, individuals with undiagnosed cardiometabolic disease have an increased risk of elevated inflammation as measured by CRP (OR 2.38; 95%CI=1.90-2.99).In conclusion, a substantial proportion of the adult population, particularly minority and low socioeconomic populations, have elevated inflammation. Systemic inflammation may be a potential focus for disease prevention and disease progression in primary care.